Fault tolerant control design for polytopic LPV systems - Rodrigues, Mickael; Theilliol, Didier; Aberkane, Samir; Sauter, Dominique (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with a Fault Tolerant Control (FTC) strategy for polytopic Linear Parameter Varying (LPV) systems. The main contribution consists in the design of a Static Output Feedback (SOF) dedicated to such systems in the presence of multiple actuator faults/failures.
Keywords: fault tolerant control; multiple actuator failures; polytopic LPV systems; LMI; static output feedback; stability